(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article is devoted to the study of psychological factors that can influence upon personal motivation and readiness for charity of adolescent. The findings can help to increase the effectiveness of programs that involve young people in charity and identify the most effective methods to form prosocial behavior of young people aimed at helping and supporting others in the long run. The purpose of the article is to investigate the influence of personal, pedagogical and socio-psychological factors on the formation of young people’s readiness for charitable activity. The author analyzed the potential positive consequences of prosocial activity for adolescents, identified the main motives of charity and the specific motivation of high school students, summarized information about the factors and mechanisms of involvement and formation of charitable readiness. Analysis of the data obtained in the empirical study of adolescents from two schools with different pedagogical environment and different levels of organization of school prosocial activity, allowed to identify a number of patterns that indicate the dominant factors in the formation of adolescents readiness for charity. We have found that altruism, empathy and the dominance of values of universalism, goodness and conformity are significant personal characteristics that determine the readiness for charitable activity. Significant personal factors are polymotivation (the combination of personal and social motives for charitable activities), a high level of involvement in such activities and the availability of certain experiences. We have found that the most important environments for development of charity readiness are the family and the school. The immediate environment (project team) and the authority of the mentor, the possibility of self-realization, the reach of the result, the opportunity to receive positive emotions, the level of responsibility play a significant role in increasing the level of involvement in school projects and programs. In a school where teachers attach great importance to the prosocial activity of students in the educational process, the impact of the school environment becomes major. It determines the readiness for further charity both with the family and as a part of extracurricular activities.